PEPITEM, its tripeptide pharmacophores and their peptidomimetic analogues regulate the inflammatory response through parenteral and topical dosing in models of peritonitis and psoriasis - Anella Saviano; Bonita Apta; Samantha Tull; Laleh Pezhman; Areeba Fatima; Mustafa Sevim; Antonio Mete; Myriam Chimen; Anna Schettino; Noemi Marigliano; Helen M. McGettrick; Asif J. Iqbal; et al. (Pharmacological Research)
PEPITEM is an immune-modulatory peptide that effectively regulates inflammation and mitigates immune-mediated inflammatory diseases (IMIDs). Here, we identify two independently active tripeptide pharmacophores within PEPITEM and engineered peptidomimetics with enhanced pharmacodynamic properties. These peptidomimetics regulate T-cell trafficking in vitro and reduce T-cell, neutrophil and macrophage numbers in the inflamed peritoneal cavity in vivo. In a plaque psoriasis model, topical administration reduced disease severity, inflammation and immune cell infiltration, while regulating cytokine release in macrophages and fibroblasts, as well as keratinocyte proliferation. Th1 and Th17 cell abundance, along with their cytokines, was reduced in secondary lymphoid organs. This expanded functional repertoire of PEPITEM and its derivatives provides innovative tools for countering immune and stromal cell-induced pathology in IMIDs. Moreover, by identifying significantly smaller tripeptide pharmacophores of 14 amino acid PEPITEM, we may be able to deliver substantial financial advantages in synthesis and formulation. The order of magnitude increase in efficacy observed for some peptidomimetics may deliver agents with enhanced pharmacological characteristics compared to the parent PEPITEM sequence. Taken together with other reports on the efficacy of PEPITEM, this study paves the way for the development and translation of a novel class of anti-inflammatory agents which may have utility in a broad range of autoimmune and chronic inflammatory diseases.